(untitled) (Journal of Foreign Language Studies, 2024)
Despite extensive research on the relationship between beliefs and practices in various aspects of second language writing instruction, studies focusing on teachers’ beliefs regarding teaching approaches to writing and the factors that shape these beliefs, particularly in higher education contexts, are scarce. This study investigated the beliefs of three university teachers regarding their instructional approaches to second language writing via in-depth semi-structured interviews. The findings reveal a discrepancy between the teachers’ preferred approaches and those they actually use. Although the teachers could flexibly implement an eclectic approach that combines both product- and process-oriented methods, they tend to prefer a single approach. In addition, the challenges preventing these teachers from implementing their preferred approaches may derive from the external factors, including the lack of professional development, large class sizes, and the low student motivation. This study emphasises the importance of providing teachers with opportunities for professional development, particularly courses focused on genrebased approaches. Such training can enhance their understanding and enable them to effectively integrate elements of all three approaches into their teaching practices within specific contexts.